Adaptive governance of the Baltic Sea – lessons from elsewhere. Issue 1 (March 2015) - Valman, Matilda; Österblom, Henrik; Olsson, Per
Governance of marine resources is increasingly characterized by integrated, cross sectoral and ecosystem based approaches. Such approaches require that existing governing bodies have an ability to adapt to ecosystem dynamics, while also providing transparent and legitimate outcomes. Here, we investigate how the Baltic Marine Environment Protection Commission (HELCOM), the international governing body for the Baltic Sea, could improve its prospects for working with the ecosystem approach, drawing from the literature on adaptive governance. We construct an ideal type of adaptive governance to which we compare the way in which HELCOM is operating and relate these dynamics to two other international marine environment governance organizations, the Coral Triangle Initiative on Coral Reefs, Fisheries and Food Security (CTI-CFF) and the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). We conclude that HELCOM deviates from an ideal type of adaptive governance in several ways but also that the other two case studies provide empirical support for potential ways in which HELCOM could improve its adaptive capacity. Key aspects where HELCOM could improve include increasing stakeholder participation – both in information sharing and decision making. Further, HELCOM need to develop evaluation mechanisms, secure compliance to improve adaptive capacity and organizational effectiveness, which entails the development of structures for conflict resolution. Finally, HELCOM need to increase communication and harmonization between different levels of authority.